Lactobacilli expressing broadly neutralizing nanobodies against HIV-1 as potential vectors for HIV-1 prophylaxis? - Kalusche, Sarah Verena; Vanshylla, Kanika; Kleipass, Franziska; Gruell, Henning; Müller, Barbara; Zeng, Zhu; Koch, Kathrin; Stein, Stefan; Marcotte, Harold; Klein, Florian; Dietrich, Ursula (Vaccines, 2020)
In the absence of an active prophylactic vaccine against HIV-1, passively administered, broadly neutralizing antibodies (bnAbs) identified in some chronically infected persons were shown to prevent HIV-1 infection in animal models. However, passive administration of bnAbs may not be suited to prevent sexual HIV-1 transmission in high-risk cohorts, as a continuous high level of active bnAbs may be difficult to achieve at the primary site of sexual transmission, the human vagina with its acidic pH. Therefore, we used Lactobacillus, a natural commensal in the healthy vaginal microbiome, to express bn nanobodies (VHH) against HIV-1 that we reported previously. After demonstrating that recombinant VHHA6 expressed in E. coli was able to protect humanized mice from mucosal infection by HIV-1Bal, we expressed VHHA6 in a soluble or in a cell-wall-anchored form in Lactobacillus rhamnosus DSM14870. This strain is already clinically applied for treatment of bacterial vaginosis. Both forms of VHHA6 neutralized a set of primary epidemiologically relevant HIV-1 strains in vitro. Furthermore, VHHA6 was still active at an acidic pH. Thus, lactobacilli expressing bn VHH potentially represent an attractive vector for the passive immunization of women in cohorts at high risk of HIV-1 transmission.